Hydroponic cultivation of crops for the rural community - Ismail, Mohd Razi; Raja Harun, Raja Muhammad (1991)
This paper discusses briefly the development of hydroponic culture system in University Pertanian Malaysia. The systems have developed from the initially used deep culture system progressing to the nutrient film technique and currently the open system using soilless substrates. The latter system using locally avaialable soilless substrates such as sand or sawdust appears to be suitable for use in rural areas. Cropyield from these simpler systems are comparable to that obtaining under the more sophisticated systems which are more costly.